State and funds of funds in venture industry development - Malashenkova, Olga F. (Journal of the Belarusian State University. Economics, 2018)
The article analyses the successful world experience that defines a role of the state and government support programs of venture business development as the start catalyst of venture processes in the country. It is shown that the programs of direct state investments basically are typical for developed countries. It is proved that the developing countries achieved success thanks to found mechanisms. The article reveals an essence of fund of funds and its role in development of the venture industry. Here are given examples of the state support of venture business in different countries: Finland, Israel, the USA, Russia, Kazakhstan. Article will be interesting as to expert – investors, economists, scientists, post-graduate students, students, and a wide range of readers.